24. EVALUATION OF SCREENING RESULTS AND EPIDEMIOLOGICAL CHARACTERISTICS OF THALASSEMIA PREGNANT WOMEN AT HUNG VUONG HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: This study aimed to evaluate the screening rate and demographic of Thalassemia among pregnant women at Hung Vuong Hospital.Subject and method: A cross-sectional study was conducted on a cohort of pregnant women who underwent screening for Thalassemia using mean corpuscular hemoglobin and mean corpuscular volume indices at Hung Vuong Hospital.Results: From January 2023 to January 2024, a total of 23,015 pregnant women were screened, with 5,372 cases (23.34%) identified as high-risk for Thalassemia. Among these high-risk cases, 63 pregnant women consented to further confirmatory diagnostic testing, revealing that 38.10% of those screened as high-risk did not carry the disease gene. The prevalence of AlphaThalassemia was notably high, accounting for 41.27%, while Beta-Thalassemia was detected in 15.87% of cases. Approximately 4.76% of pregnant women were found to have both Alpha and Beta-Thalassemia. Among those diagnosed with Alpha-Thalassemia, the SEA heterozygous genotype was the most prevalent (68.97%). In the Beta-Thalassemia group, the HBE heterozygous genotype was the most common, comprising 34.48% of cases.Conclusion: The rate of Thalassemia gene carriers is high, especially among ethnic minorities, with Alpha-Thalassemia being predominant. Expanding screening and appropriate management of iron deficiency plays a crucial role in improving health for pregnant women.
Keywords: Thalassemia; đặc điểm dịch tễ; Việt Nam; sàng lọc